František Herites's salon prose - Dušková, Pavlína (Bohemica Olomucensia, 2020)
František Herites published a prose with clear signs of salon literature (a salon room, a salon speech, a romantic story) in the periodical Lumír. Further Herites's prose is dominated by decorative descriptions, floral ornaments associated especially with female heroes, these ornaments symbolize their beauty and uniqueness (the influence of Parnassian literature). And finally in his prose we find ever-colliding idyllic and anti-idyllic elements, for example topos of idyllic places and boats versus the tragic death of the main character.
Keywords: Salon prose; romanticism; biedermeier; idyll; parnassianism; floral ornament; decoration